Adnexal Torsion in the Third Trimester of Pregnancy After in Vitro Fertilization: A Case Report - İlker Selçuk; Gökhan Boyraz; İbrahim Esinler (Gynecology Obstetrics & Reproductive Medicine)
Adnexal torsion causes venous and lymphatic blockade complicated by congestion. Adnexal torsion is seldom in pregnancy, occuring approximately 1 in 5000 pregnancies, more frequently in the first trimester. Acute abdominal pain and abdominal disturbances are challenging issues during pregnancy for the diagnosis. The clinical symptoms are non-specific. Colour and power Doppler sonography may be useful for the early diagnosis. Adnexal torsion is generally due to ovarian stimulation treatment or ovarian masses in pregnancy. The correct diagnosis of maternal ovarian torsion might be delayed or underestimated in the second half of gestation because the increased dimensions of the uterus could blockade the abdominal palpation and make the sonography inefficient. Laparoscopy should be preferable for the adnexal torsion suspicion. But as the gestational age increases laparotomy should be a choice because of the risk of injury to the uterus related to the enlarged volume by the fetus.